The Relationship Between Parental Reflective Function, Attachment and Development of Child Psychopathology - Magdalina Koycheva (Педагогически форум)
This article presents a theoretical overview of the relationship between parental reflective function, attachment style and the development of child psychopathology. The concept of parental reflective function was developed by Peter Fonaghi and his colleagues. Reflexive functioning is defined as the ability to imagine our mental states, emotions and desires, as well as those of others. The ability to interpret and integrate past relational experience is seen as a high capacity for parental reflection. Central constructs in the theory of attachment are: the sensitive response of the mother, the internal working models and representations, the quality of attachment and the sense of security. In the process of developing attachment, the child builds Internal working models, which are formed on the basis of real relationships and participate in building representations of relationships. Arieta Slade and her colleagues believe that higher levels of reflective functioning are associated with secure attachment in children and conversely lower levels of reflective functioning are associated with insecure attachment in children, such as mothers of children who resist and are disorganized, they have the lowest levels of reflective functioning. Low levels of reflective functioning allow the baby's adaptive mechanisms to be distorted and to develop the pathological ways of interaction with the parent.